Iranians’ Unauthorized Mobility Projects to Europe: A Digital Ethnography of Smuggling and Solidarity - Ghaffari, Rassa (PARTECIPAZIONE E CONFLITTO, 2025)
In the last decades, Iran has witnessed an increasing development of the culture of migration due to several political, social, and economic causes. This has led to the widening and specialization of the corresponding migration industry, with the role of the so-called digital infrastructure evolving in creative and innovative ways. Relying on several months of digital ethnography on virtual platforms used by Persian-speaker individuals to share information about border crossing, this paper aims to shed light on some under-represented strategies and practices of self-determination of Iranian citizens who plan to irregularly reach Europe as their final or intermediate destination. By doing so, it intends to problematize some perspectives that have long informed contemporary migration studies, such as the figure of the smuggler and the multifaced concept of solidarity informing these virtual networks. The data partially challenges the categorization of smugglers as ’evil villains’ through an exploration of the moral economy of smuggling. Often depicted as pure victims, Iranians illegally moving never cease to have aspirations and remain subjects who make more or less calculated tactical choices about how to reconfigure their lives and advance their projects. The decision to move is interpreted in light of the migration autonomy approach, which focuses on the generative, exceeding, and multiple dimensions of migration movements.